Factors associated with the mobbing in teachers of the university national Hermilio Valdizán. Huanuco - 2014 - Tamayo Garcia, Mónica Roxana (2017)
The mobbing or bullying in labor organizations is a problem that significantly affects the efficiency of human resources, harming the health of the workers affected, causing your low labor and its psychological and physical deterioration. The research was conducted with the objective to determine the factors associated with the mobbing in teachers of the National University of Huánuco Hermilio Valdizán. The type and level of investigation was correlational, descriptive, explanatory, applicatives, analytical, prospective and cross-sectional with a sample of 100 teachers appointed that met the selection criteria, they represent 26.4 % of the population of teachers appointed by the University, such as sample frame was the records of teachers by powers and the unit of analysis consistedof teaching the victims of mobbing that working in the UNHEVAL. For the data collection used thequestionnaire and use has been made of the survey as a technical one. The main findings werethat as a result of mobbing a 14% of the teachers present low mood and depression, 10% haveheadaches, a 7% far cry and cry and a 6% assume the mental health problem isolating themselvesfrom their environment and how they manifest themselves prefer to withdraw from any activityand social relations, while a 5% presents apathy and lack of initiative in their work environmentand another 5% reported difficulty with concentration, is also warn that the 3% indicates difficultysleeping for inferring that the teachers will have other mental health disorders in addition to theinsomnia, also a 2% of teachers presents irritability followed by another 2% reported having feelingsof insecurity, and it is worth mentioning in an alarming way that 1% of the teachers in studypresents thoughts of suicide, is highlighted with regard to psychological abuse occurred in the workenvironment, where the majority (63 %) of teachers in study, indicate that they were and are victimsof psychological mistreatment in the UNHEVAL. And in regard to the authors of the Psychologicalabuse at the University, it should be noted that 47% of teachers reported that the authors of thepsychological violence are the authorities, managers and heads of the University, followed by a 13%of teachers who said the same co-workers are the aggressors psychological.